Evaluation of practices of self-medication among undergraduate dental students in Riyadh - Umbreen Noor Muhammad (Wolters Kluwer Medknow Publications, 2021)
Introduction: Self-medication (SM) and purchase of over-the-counter medication have been in practice in medical fields. Dental students have the knowledge of pharmacological drugs and they have a higher chance than the population to indulge in SM. Aim: The aim of the study was to evaluate the practice, awareness, and attitude of undergraduate dental students toward SM and its relation with gender and to assess whether this practice differs among students of different years of study. Methods: A cross-sectional survey was conducted using simple random sampling among undergraduate dental students in a private dental college in Riyadh. A self-designed online questionnaire was used to collect data, which was validated and used for the research Results and Discussion: A total of 465 students (31% males and 69% females) responded to the survey. 60% of the students agreed to practice SM and it was significantly (P < 0.05) higher in females than males. With each successive year of study, there was significant decrease (P < 0.05) in the practice of SM and significant increase (P = 0.000) in the level of awareness toward SM. Body aches (57%) and mouth ulcers (35%) were the most common indications to practice SM regarding general and oral health, respectively. Most commonly used medicines were analgesics. Previous experience to treat the same illness was the most common reason for practicing SM, and the primary source of medicine was the medicine present at home. Conclusion: More than half of the respondents practiced SM for minor illnesses, and it was higher among females and students of preparatory years. There was less awareness among dental students relating to survey items such as importance of completing the course of medicine and adverse drug reactions. This study highlights the need to develop awareness and interventions to assess this health problem among dental undergraduates.